2012
DOI: 10.5294/laclil.2012.5.2.9
|View full text |Cite
|
Sign up to set email alerts
|

CLIL implementation in Italian schools: can the long ago employed teacher be trained effectively? The Italian protagonists’ voice

Abstract: Most Italian upper schools will have to offer at least one subject in a foreign language as part of the national curriculum as of the 2012-2013 scholastic year. This paper reports the results of a survey carried out between April and June 2011 in order to get the feel of the teachers' expectations, concerns, and other thoughts in the wake of Italy's "CLIL revolution". The intention is to offer those in charge of the project a chance to hear the voices of the teachers being asked to take on the task, requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Secondary school mathematics teachers in Italy were asked about their attitudes to different aspects of CLIL (Favilli, Maffei, & Peroni, 2013), and they reported a number of difficulties related to their linguistic ability. A similar study in Italy by Di Martino and Di Sabato (2012) found negative attitudes towards the quite sudden imposition of EMI at the upper secondary level without adequate teacher or student preparation. Thus, one of the themes that sometimes arises in the EMI teacher beliefs literature is the extent to which the stakeholders (in this case teachers) are involved in the decision to introduce it, to what extent and when.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Secondary school mathematics teachers in Italy were asked about their attitudes to different aspects of CLIL (Favilli, Maffei, & Peroni, 2013), and they reported a number of difficulties related to their linguistic ability. A similar study in Italy by Di Martino and Di Sabato (2012) found negative attitudes towards the quite sudden imposition of EMI at the upper secondary level without adequate teacher or student preparation. Thus, one of the themes that sometimes arises in the EMI teacher beliefs literature is the extent to which the stakeholders (in this case teachers) are involved in the decision to introduce it, to what extent and when.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Authors Di Martino and Di Sabato (2012) highlight the innovation that CLIL has brought to the Italian educational system in terms of improved language performance and better mastery of subject contents in a foreign language. The same authors, however, also point out that CLIL methodology requires a series of actions to be taken that need to be standardized, systematic and operational.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on teacher professional development in CLIL appears to be a less-researched area in Italy (Coonan, 2011;De Santo & De Meo, 2016;Di Martino & Di Sabato, 2012), over the last twenty years, many different kinds of university-run professional development programmes in CLIL have been offered to in-service Italian teachers. In the last years, the general trend towards blended coursesthat is, courses where part of the traditional face-to-face instruction is replaced by web-based online learningis witnessed in the CLIL training context as well: not only does this have to do with feasibility, as online sessions allow for better time investment and management, but also with the fact that teachers can be introduced to affordable and useful technologies.…”
Section: The Role Of Blended Training In Clil Teacher Training In Italymentioning
confidence: 99%